2000
DOI: 10.1053/ejvs.2000.1195
|View full text |Cite
|
Sign up to set email alerts
|

Occlusive Arterial Disease in HIV-infected Patients: a Preliminary Report

Abstract: initial experience with large-vessel occlusive disease in HIV positive patients suggests an underlying arteritic aetiology, with clinical and pathological features distinct from atherosclerosis. Further in-depth study is necessary to clarify the pathophysiological basis thereof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Gisselbrecht et al identified 8 cases of vasculitis among 450 HIV-infected patients, among which 5 met the classification criteria of polyarteritis nodosa [23]. Vasculitis associated with arterial thrombosis has been reported by Nair in 20 young patients from South Africa [26]. A clinicopathologic evaluation has been performed by Gherardi et al who found 34 inflammatory vascular diseases among muscle, nerve or skin biopsy specimens from 148 HIVinfected patients.…”
Section: Inflammatory Vasculitismentioning
confidence: 99%
“…Gisselbrecht et al identified 8 cases of vasculitis among 450 HIV-infected patients, among which 5 met the classification criteria of polyarteritis nodosa [23]. Vasculitis associated with arterial thrombosis has been reported by Nair in 20 young patients from South Africa [26]. A clinicopathologic evaluation has been performed by Gherardi et al who found 34 inflammatory vascular diseases among muscle, nerve or skin biopsy specimens from 148 HIVinfected patients.…”
Section: Inflammatory Vasculitismentioning
confidence: 99%
“…41,42 These abnormalities have been associated with documented thromboses involving both veins and arteries and seem to be related to PIcontaining HAART. 41,43,44 Thrombocytosis has been reported in 9% of patients receiving HAART, with cardiovascular complications in up to 25% of the cases. 45 According to the Pavia Consensus Statement, the routine evaluation of coagulation parameters is probably not advisable until the benefit of widespread screening is assessed in prospective studies.…”
Section: Haart and Coagulation Disordersmentioning
confidence: 99%
“…HAART-induced insulin resistance may cause increased sympathetic activity and sodium retention, potentially leading to hypertension [42,43]. Recent reports indicate that elevated blood pressure may be related to PI-induced lipodystrophy and metabolic disorders, especially to fasting triglyceride levels [44].…”
Section: Haart Hypertension and Coagulative Disordersmentioning
confidence: 99%
“…Moreover, HIV-infected patients, especially those with fat redistribution, may develop coagulation abnormalities such as increased levels of fibrinogen, D-dimer, plasminogen activator inhibitor-1 and tissue-type plasminogen activator antigen, or deficiency of protein S [45,46]. These abnormalities have been associated with documented thromboses involving both veins and arteries and seem to be related to PI-containing HAART [43,45]. In a large multicentre epidemiologic survey, Sullivan et al reported an incidence of clinically recognized thrombosis of 2.6/1000 person/year in a sample of 42,935 HIV-infected adults.…”
Section: Haart Hypertension and Coagulative Disordersmentioning
confidence: 99%